Combination of TRIZ and Additive Manufacturing Methods: A Literature Review - Van Hubert; Rosnani Ginting; Aulia Ishak (Jurnal Sistem Teknik Industri, 2025)
Companies face pressure to enhance productivity and efficiency while meeting the demands of dynamic markets and global competition. Additive Manufacturing (AM) technology has emerged as an innovative solution with the capability to efficiently create complex geometries and enable design personalization, despite ongoing challenges related to quality, materials, and post-processing. The TRIZ method, as a systematic problem-solving approach, offers innovative solutions by analyzing contradictions in design, which can be applied to AM to optimize processes and products. The Design for Additive Manufacturing (DFAM) approaches leverages AM's layer-by-layer production process to create new, innovative designs. In the context of Concurrent Engineering (CE), the synergy between CE, AM, and TRIZ enables more efficient, innovative, and rapid product development, providing design flexibility, lower production costs, and shorter time-to-market. This combination of strategies offers a significant competitive advantage in the global market.